Early childhood caries risk indicators among preschool children in rural Egypt: a case control study - Dina Attia; Mona K. ElKashlan; Susan M. Saleh (BMC, 2024)
Abstract Background Early childhood caries (ECC) is a public health problem, especially in developing countries like Egypt which has an ECC prevalence of 74%. This research aimed to assess the risk indicators associated with ECC in a rural, socially-disadvantaged population in Alexandria, Egypt. Methods A case-control study was conducted in 8 nurseries of preschool children aged 3 to 5 years in rural, deprived areas in Alexandria, Egypt, from October 2019 till January 2020. Two groups, 93 with ECC and 93 without ECC. A validated questionnaire was used to collect sociodemographic data including age, sex, number of siblings, socioeconomic status, oral health practices including toothbrushing frequency, pattern of dental visits, daily frequency of sugary snacks. Also, salivary pH and buffering capacity were assessed. A trained and calibrated dentist assessed caries status clinically according to the World Health Organization (WHO) criteria using the dmft index and oral hygiene status using Silness and Loe Plaque Index. Chi-squared test, followed by multivariable logistic regression were performed to assess the relation between independent variables and ECC, P < 0.05 was considered to be statistically significant. Results Bivariate analysis showed that age, mother's education, dental visits, dietary habits, Plaque index, salivary pH and buffering capacity were significantly associated with ECC. The significant risk indicators for ECC in multivariable regression were age (AOR = 4.73, 95% CI: 2.76-7.83), mother's education (illiterate vs. university educated, AOR = 28.36, 95% CI: 8.51-112.92), frequency of daily sugary snacks (twice vs. once, AOR = 2.00, 95% CI: 1.29-3.49, and three or more vs. once, AOR = 2.67, 95% CI: 1.72-3.27), night feeding (AOR = 1.89, 95% CI: 1.38-10.21), Plaque index (AOR = 21.34, 95% CI: 5.56-81.99), and salivary pH (AOR = 0.16, 95% CI: 0.05-0.58). Conclusion This study suggests that sociodemographic indicators, dietary habits, plaque accumulation and salivary pH are risk indicators for ECC in the studied population.